Pengaruh Penggunaan Suhu Perendaman Berbeda Terhadap Mutu Surimi Ikan Lele Dumbo (Clarias gariepinus) - Saparudi Saparudi; Desmelati Desmelati; Rahman Karnila (Berkala Perikanan Terubuk, 2015)
The objective of this research was to investigated the effect of soaking the fish in different water temperature on quality of surimi produced. Farm raised catfish weighing 300-400 g each, was filled, washed, ground and soaked into different chilled water temperature (5°C, 10°C, 15°C and 20°C) for 10 minutes, and made for surimi. The surimi were evaluated for gel strenght (fold and bite test), pH,  protein and ash. The Research was designed using a completely randomized design (CRD), and the difference between treatments were tested by Duncan test. The result indicated that the surimi prepared by soaking the fish in chilled water (15°C) was the best quality of surimi (fold value : 4,6 and bite value : 7,5). The composition of protein, fat and ash of surimi soaked in the chilled water (15°C) was 15.1 % , 0.4 % and 6.3% respectively.